MEMBANGUN MASYARAKAT BERBUDAYA MELALUI BAHASA INDONESIA - Maimunah, Siti Annijat (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2014)
Language and literature are two different side of coin but cat be separated, because language is mirror of culture and identity of the speakers. It means that, whether language can influence the culture of society or vice versa?, therefore language can determine the progress and â€œextinguishâ€ the culture of nation. As we know that there are so many local languages which experience it. Language and culture are two studies that complement each other. Culture kept alive if constructed by language as the medium. Both of them have the same purpose, is bringing people to achieve better life, more humane, well-organized, more religious, and more dignified. There is occur reciprocal relationship that determine between language, culture, and society that embodies both.Â  Developed and praiseworthy civilization and culture upheld by society is reflected through language that used in order to create civilization and culture that built. Â Â Keywords: Civilized Society, Indonesia Language